Jewishness as sui generis: extending theorizations beyond the debate of "race, ethnicity, or religion". Issue 3 (19th February 2020) - Gonzalez-Lesser, Emma
ABSTRACT: Scholarship on Jewishness has often assumed that race, ethnicity, and religion are discrete categories. This review article surveys the place of Jewishness within race literature, ethnicity literature, and sociological religion literature, and offers a new theoretical framework for considering Jewishness as sui generis – of its own unique quality. The categories of race, ethnicity, and religion must be theorized as a system of interconnected frames and processes that overlap, interact, and are co-constituted . This web of frames and processes must be situated within the larger social system and meanings that construct Jewishness alongside other subjectivities .